PENGGUNAAN APLIKASI ITEM AND TEST ANALYSIS (ITEMAN) PADA SOAL TRY OUT UN IPA SMP TAHUN 2019 - Nuril Huda; Tutik Sri Wahyuni (Prodi Pendidikan IPA FMIPA Universitas Negeri Malang, 2020)
The aims of this study are to (1) determine the use of ITEMAN application in analyzing try out of Junior High School Sciences National Exam; 2) find out the number of good questions based on classical test theory (CCT). This research is a descriptive study with a quantitative approach. The data source is from the Student Answer Sheet in Tulungagung Regency with a random sample of 1,777. Data collection techniques with documentation. The results of this study: 1) the use of ITEMAN application in analyzing the items obtained: a) the value of the reliability coefficient alpha = 0.84 (very high), split-half (first-last) = 0.72 (high), and S-B (first-last) = 0.84 (very high) and measurement error of 2.41; b) difficulty level: 3 items (10.00%) are easy, 24 items (80.00%) are moderate, and 3 items (10.00%) are difficult; c) discrimination: 3 items (10.00%) are bad, 6 items (20.00%) are good enough, 5 items (15.67%) are moderate, and 16 items (53.33%) are good; and the effectiveness of the distractor: 27 items (90.00%) the distractor functionate, and 3 items (10.00%) the distractor does not function. 2) There are 19 items (63.33%) good questions based on CCT, they can be stored as question bank.